Characterization of GaN-based HEMT structures for high power applications - Pang, Shi Xiang. (2013)
GaN based HEMT devices on 4 inch Si (111) were characterized to study their electrical parameters, using Hall Effect, Current-Voltage and Capacitance-Voltage measurements. Four different types of structure configurations were studied, which include different stress mitigating layers with carbon doping of the GaN buffer. The effect of carbon doping on the electrical parameters and the buffer leakage current were analyzed. The threshold voltages and the doping concentration were comprehensively studied to determine the background carrier concentration.